Dielectric Breakdown Strength of Polypropylene Blended with Ethylene Octene Elastomers (ELEKTRIKA- Journal of Electrical Engineering, 2023)
Polymer blends have become a major focus of research in exploring the potential for new dielectric material applications, particularly in the insulation of high voltage systems. In the current research area, polypropylene (PP) is being investigated as an insulation material for high voltage alternating current and direct current power cables. However, PP must be treated with rubbery materials such as elastomers to lessen its overall stiffness for power cable extrusion. While various promising results have been published on the potential use of PP/elastomer blends as dielectric materials, the dielectric effects of adding ethylene octene elastomer to PP have been less explored. This paper discusses the alternating current (AC) and direct current (DC) breakdown strength of PP that contains different amounts of ethylene octene elastomer (10, 30, and 50 wt%). The addition of ethylene octene elastomer to PP affects the breakdown performance of the blend systems under both AC and DC fields. Significantly, an increase in elastomer contents results in a notable reduction in the AC and DC breakdown strength. A discussion is presented on the mechanisms underlying the change in the breakdown strength caused by the different amounts of ethylene octene elastomer blended with PP.